PERBANDINGAN HASIL UJIAN NASIONAL ANTARA SEKOLAH DASAR YANG MENGGUNAKAN KTSP DENGAN SEKOLAH DASAR YANG MENGGUNAKAN KURIKULUM 2013 DI KECAMATAN WIH PESAM KABUPATEN BENER MERIAH - M. Nasir Yusuf M. Nasir Yusuf.; Mirawati Mirawati. (Jurnal Pesona Dasar, 2017)
The research aims at finding out the result of national examinationof two schoolsthat used school-based curriculum and K-13 curriculum. The research hypothesis is that there is a significant difference on the result of national examination in 2016 taken from both schools. The research approach is quantitative approach with comparative study. The data that is obtainedfrom the schools areanalyzed using “t” formula for difference test. Based on the result of data analysis, t test is -2.86154 and t table is 2.000.In conclusion, there is a significant difference on the result of national examination between a school with school-based curriculum and a school with K-13 curriculum. In conclusion, a school-based curriculum school got better result than a K-13 curriculum school did.